Constructive and destructive workplace deviance: a review - Ng, Lei Voon; Othman, Mohamad Hashim; Chan, Siaw Leng (Faculty of Agriculture and Food Sciences, Universiti Putra Malaysia Bintulu Sarawak Campus, 2019)
Workplace deviance receives increasing research due to its remarkable impact on the well-being of organization and employees. Constructive deviance appears to bring about both positive and negative consequences when putting together its outcomes. Despite the negative consequences of workplace deviance in most organizations, little to no interest has been shown in managing minor destructive deviant behaviours which may escalate to major drawbacks on both the organization’s entire output as well as the individual employee’s moral and motivation. The authors reviewed the distinctive yet interrelated definitions, types, contributing factors, and consequences of both constructive and destructive workplace deviance that should not be underestimated. This paper included a sample of cognitive behavioural theory-based counselling and coaching intervention for narcissistic organizational leaders.